The effect of the FRESH end-to-end approach in Tanzania on agricultural production and diet intake: Statistical analysis plan - Bliznashka, Lilia; Azupogo, Fusta; Olney, Deanna K.; Kumar, Neha; Kinabo, Joyce; Hess, Sonja; Arnold, Charles D. (Center for Open Science, 2024)
In Tanzania, undernutrition and overnutrition are pressing public health issues. The latest Demographic and Health Survey shows that 36% of women of reproductive age are overweight or obese and 42% are anaemic. Poor diets, including low fruit and vegetables (F&V) intake, are a major contributor to non-communicable diseases (NCDs) and associated morbidity and mortality globally. In 2012, a national survey found that 95% of Tanzanians consumed insufficient F&V.